A chip-based microcavity derived from multi-component tellurite glass. Issue 20 (28th May 2015) - Zheng, Binbin; Zhao, Mingxiao; Guo, Qiangbing; Yu, Yongze; Lu, Shichao; Jiang, Xiaoshun; Zhou, Shifeng
<x xml:space="preserve">Abstract</x> Our results provide the first prototype of a chip-based optical microcavity derived from multi-component tellurite glass.